What Is Behind the ifo Business Climate? Evidence from a Meta-Survey - Stefan Sauer; Klaus Wohlrabe (CESifo GmbH, 2024)
The ifo Business Climate Index is considered as one of the most important leading indicators for the German economy. It is based on a monthly survey of about 9,000 companies located in Germany and composed of two main questions from the monthly questionnaire: the assessment of the current business situation and the business expectations for the next six months. The terms 'business situation' and 'business expectations' are formulated deliberately vague and not explicitly defined. Thus, each survey participant can consider its own main driving factors. But what are these underlying factors? Do they differ between sectors or by firm size? To answer these questions, we conducted a meta-survey among all survey participants. The results suggest, that especially internal company factors, such as the profit situation, demand, and turnover, are crucial. Generally, using a principal component analysis we show, that these factors can be decomposed into three components: (1) the overall financial situation, (2) the demand and order situation, and (3) external influences. Our findings provide some insights concerning the high predictive power of the ifo Business Climate Index and its components. Furthermore, the identified factors might also be useful for business cycle analyses in practice.
Keywords: C53; C83; L20; 330; ifo Business Climate; business expectations; business situation; meta-survey